Which is the simplified form of the expression
( (2^{-3})(x^{-3})(y^{2}) )^{2}
( (4^{-2})(x^{4})(y^{6}) )?
1
1/4x^{2}y^{16}
4/x^{2}y^{16}
1/4x^{14}y^{8}
4/x^{14}y^{8}
Share
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
To simplify the expression ( left( (2^{-3})(x^{-3})(y^{2}) right)^{2} left( (4^{-2})(x^{4})(y^{6}) right) ), we will break it down step-by-step.
1. Simplify ( (2^{-3})(x^{-3})(y^{2}) ):
– When raised to the power of 2:
[
(2^{-3})^2 = 2^{-6}, quad (x^{-3})^2 = x^{-6}, quad (y^{2})^2 = y^{4}
]
– Thus, ( (2^{-3})(x^{-3})(y^{2}) ) becomes:
[
2^{-6} x^{-6} y^{4}
]
2. Combine the simplified expression:
[
(2^{-6} x^{-6} y^{4}) = 2^{-6} x^{-6} y^{4}
]
3. Now simplify ( (4^{-2})(x^{4})(y^{6}) ):
– Note that ( 4 = 2^2 ), so ( 4^{-2} = (2^2)^{-2} = 2^{-4} ):
[
(4^{-2}) = 2^{-4}, quad